Estudo molecular de Astyanax altiparanae Garutti & Britski 2000 (Teleostei: Characidae) como provável complexo de espécies - Deprá, Ígor de Carvalho (2013)
In the last decade, ten species from the genus Astyanax Baird e Girard 1854 have been described, and several non-described ones have been reported recently. Astyanax altiparanae Garutti & Britski 2000, occurring in the upper Paraná River basin, belongs to the bimaculatus group, which comprises a number of species with very similar color pattern and morphology, resulting in they being cryptic. Following the advances in species diagnosis using mitochondrial DNA data, highly divergent D-loop lineages have been found previously in A. altiparanae, which have been distinguished as AltoPR and AltoPR-D groups. This evidence suggests that individuals carrying these mitochondrial lineages do not belong to the same species. By using cox1 gene sequences, genetic distances between them were calculated with Kimura-2-parameter (K2P) model gamma-distributed (parameter 0.09); sequences available at GenBank were included. Maximum likelihood and maximum parsimony phylogenetic analyses were conducted. Within-group mean distances for AltoPR and AltoPRD were, respectively 0.02 and 0.03, and net mean distance between them was 0.34. The sequences from individuals collected in Paraíba do Sul River basin also form two groups with distances compatible to those of congeners, one of which was identified as AltoPR. Nonetheless, the other group showed an intermediate value when compared to AltoPR-D, and should be further investigated. The rest of the included species are less close to these and appeared monophyletic in both trees, with very high bootstrap values. The results point to a species status of both lineages, one of which is probably new.